Attachment of Cell Walls of Chlamydia psittaci to Mouse Fibroblasts (L Cells) - Levy, Nancy J. (1982)
(14)C-labeled cell walls of the 6BC strain of Chlamydia psittaci, prepared from intrinsically labeled chlamydial cells by digestion with deoxycholate and trypsin, associated with mouse fibroblasts (L cells) in a manner comparable to that of intact C. psittaci. Almost half of the host cell-associated cell walls were not dissociated by trypsin, suggesting that they had been attached and then ingested. The attachment of cell walls to L cells was inhibited by a number of treatments known to block association of intact C. psittaci with L cells: heating the cell walls for 3 min or reacting them with antiserum against intact C. psittaci, or pretreating the L cells with trypsin or wheat germ agglutinin. Unlike intact cells of C. psittaci, cell walls were not immediately toxic for L cells, and they did not measurably adsorb neutralizing antibody. As revealed by making cell walls from intact C. psittaci labeled with (125)I by lactoperoxidase-catalyzed iodination, cell walls contained a much smaller number of surface-labeled proteins than did whole chlamydial cells. The most abundant surface-labeled protein was one with an apparent molecular weight of 43,000. In the final step of cell wall preparation, tryptic digestion of deoxycholate-extracted cells, this major surface protein was partially cleaved to a 40,000-dalton product. When the major surface protein (both the 43,000- and 40,000-dalton moieties) was electrophoretically separated from the other cell wall proteins and used to immunize a rabbit, antibodies that neutralized the infectivity of intact C. psittaci were elicited. It was concluded that cell walls retain the ability to associate with L cells in much the same way as do intact cells of C. psittaci, but, despite the simpler structure of cell walls, the element that binds C. psittaci to host cells cannot yet be identified.